Dl-3-n-butylphthalide attenuates cerebral ischemia/reperfusion injury in mice through AMPK-mediated mitochondrial fusion - Zhu, Ting; Dong, Shanshan; Qin, Na; Liu, Rujuan; Shi, Liuliu; Wan, Qi (Frontiers in Pharmacology, 2024)
NBP is a compound isolated from celery seeds, which was approved by the National Medical Products Administration in 2002 for clinical treatment of ischemic stroke. However, in brain ischemia/reperfusion (I/R) injury, the related research on mitochondrial dynamics and its mechanism of action of NBP still need to be further studied. The aim of this study was to assess NBP on cerebral pathology in ischemic stroke in vivo, with a specific focus on the molecular mechanisms of how NBP promotes mitochondrial fusion. Male C57BL/6 mice were utilized in this study and were subjected to middle cerebral artery occlusion/reperfusion (MCAO/R).Pre-ischemia, NBP was administered through intraperitoneal (i.p.) injection for 7 days.2 Our findings demonstrated that NBP effectively reduced infarct volume, improved neurological dysfunction, enhanced cerebral blood flow, and promoted mitochondrial fusion in mice subjected to MCAO/R. More importantly, the pro-fusion effects of NBP were found to be linked to the activation of AMPK/Mfn1 pathway, and with the activation of neurological function, which was partially eliminated by inhibitors of AMPK. Our results revealed that NBP is a novel mitochondrial fusion promoter in protecting against ischemic stroke through the AMPK-mediated Mfn1. These findings contribute to the understanding of novel mechanisms involved in the protection of neurological function following NBP treatment for ischemic stroke.